Actinomycotic Mastoiditis Complicated by Sigmoid Sinus Thrombosis and Labyrinthine Fistula. (November 2014) - Lezcano, Cecilia; Simons, Jeffrey P.; Colman, Kathryn L.; Cohen, Michael S.; Lin, Philana L.; Reyes-Múgica, Miguel
Actinomyces is a rare pathogen that can be the cause of infections in the digestive and urinary tracts, skin, genitalia, and lungs, which generally have an indolent clinical course. However, in some cases these can be locally destructive and become generalized infections. Actinomyces has been previously implicated in infections of the middle ear, nasopharynx, and sinuses, occasionally causing complications such as chronic mastoiditis. Here we describe the case of a 10-year-old-male presenting with nausea, vomiting, and headache who developed intracranial complications of actinomycotic mastoiditis.